PSYCHOLOGICAL FACTORS IN DEVELOPING CIVIC IDENTITY AMONG HIGH SCHOOL STUDENTS (Multidisciplinary Journal of Science and Technology, 2025)
This article examines the psychological determinants of civic identity in high school students within the context of Uzbekistan. The study analyzes key factors such as self-awareness, emotional intelligence, socio-cultural values, and motivation, and presents conclusions related to the national and social characteristics of our country